On Certain Type of Sequence Spaces Defined by ð‹ âˆ’ Function - E Herawati; Gultom, S N R (Talenta Publisher, 2019)
In this paper, we introduce non-negative real valued ðœ‘ âˆ’ function on â„ . Using ðœ‘ âˆ’ function, we define the sequence spaces ð‘Š (ð‘“), ð‘Š 0 (ð‘“), and ð‘Š âˆž (ð‘“). We will study some topological properties defined by certain paranorm of these spaces.